1985
DOI: 10.1002/cne.902310207
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of brain alpha1‐adrenergic receptors: In vitro autoradiography with [125I]‐heat

Abstract: Much useful information on the localization of alpha 1-adrenergic binding sites has been gained by using tritiated radioligands for in vitro autoradiography. However, the iodinated alpha 1-adrenergic antagonist HEAT [( 2-beta (4-hydroxyphenyl)-ethylaminomethyl)-tetralone], BE 2254), a radioligand with high affinity and specificity, provides autoradiographs with a higher signal to noise ratio. This has allowed us to describe the anatomy of these binding sites in much greater detail than previously possible. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(117 citation statements)
references
References 115 publications
14
102
1
Order By: Relevance
“…That the effect of TER on the threshold frequency was due to its action on the LC and not some neighboring nucleus is supported by the fact that the infusion of the drug some distance away from the LC (0.3 mm or greater) greatly attenuated its effects. This is consistent with the fact that the LC possesses the greatest concentration of a 1 -receptors by far in the rodent dorsal pons (Jones et al, 1985;Stone et al, 2004a). However, this does not mean that a 1 -receptors in other brain regions are not involved in positive reinforcement; in fact, a 1 -agonists injected in the rostral ventrolateral medulla have been found to support CPP (Hirakawa et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…That the effect of TER on the threshold frequency was due to its action on the LC and not some neighboring nucleus is supported by the fact that the infusion of the drug some distance away from the LC (0.3 mm or greater) greatly attenuated its effects. This is consistent with the fact that the LC possesses the greatest concentration of a 1 -receptors by far in the rodent dorsal pons (Jones et al, 1985;Stone et al, 2004a). However, this does not mean that a 1 -receptors in other brain regions are not involved in positive reinforcement; in fact, a 1 -agonists injected in the rostral ventrolateral medulla have been found to support CPP (Hirakawa et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
“…a 1 -Adrenoceptors have a widespread distribution in the CNS and affect behavioral activity from multiple regions. The region whose a 1 -receptors have the greatest effect on behavioral activity is the dorsal pons and most likely in the locus coeruleus (LC), which also has one of the highest densities of these receptors in the brainstem (Stone et al, 2004b;Jones et al, 1985). Furthermore, the LC is a site from which self-stimulation can be elicited (Yadin et al, 1983), is highly sensitive to appetitive operant conditioning (Clayton et al, 2004) and has efferent connections with dopaminergic neurons in the ventral tegmental area (Grenhoff et al, 1993;Mejias-Aponte et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have confirmed that there is a moderately high density of a 1 -receptors in the cerebellum of the mouse strain used in the above experiments (male Swiss Webster) (Stone EA, Ahsan R, and Lin Y, unpublished results). As noted above, the nucleus accumbens also possesses a 1 -receptors but at a lower density (Jones et al, 1985).…”
Section: Brain Localizationmentioning
confidence: 73%
“…It should be noted that two of the above definite sites, the dorsal pons and DR, are known to possess very high densities of a 1 -receptors (Chamba et al, 1991;Jones et al, 1985;Zilles et al, 1993), whereas the cerebellum has been reported by some (Acosta-Martinez et al, 1999;Jones et al, 1985;Zilles et al, 1993), but not others (Palacios et al, 1987), to have a moderately high density. We have confirmed that there is a moderately high density of a 1 -receptors in the cerebellum of the mouse strain used in the above experiments (male Swiss Webster) (Stone EA, Ahsan R, and Lin Y, unpublished results).…”
Section: Brain Localizationmentioning
confidence: 95%
See 1 more Smart Citation